Regeneration of T cells from human-induced pluripotent stem cells for CAR-T cell medicated immunotherapy - Chen, Yanyan; Huang, Pufeng; Niu, Mengda; Tian, Chuanhuizi; Zhang, Tingting; Peng, Zhiping (Frontiers in Bioengineering and Biotechnology, 2023)
Background Chimeric antigen receptor (CAR) T cell treatment involves in vitro production of T cells from patient blood with synthetic receptors specific to a cancer antigen. They circumvent the major histocompatibility complex to recognize the tumor antigen, reducing hematologic malignancy remission rates by 80%. Considering the efficacy of CAR-T treatment, the present work aimed at generating functional clusters of differentiation (CD)8+ T cells from human induced pluripotent stem cells (hiPSC) and to generate hiPS-CAR-T cells with high antigen-specific cytotoxicity. Methods The Alkaline phosphatase assay and MycoEasy rapid mycoplasma detection kit was implemented for detection of hiPSCs and mycoplasma, respectively. The CD34+ HSPCs were harvested in AggreWellTM 400 using a 37-micron reversible strainer. Likewise, the lymphoid progenitor and CD4+CD8+ DP T cells were also harvested. The Cell Counting Kit-8 (CCK-8) assay was used to mark cytotoxicity and ELISA was used to detect IFN-γ secretion. Further, flow cytometry and transwell chambers were used to assess cell cycle, and migration and invasion. Finally, the in vivo antitumor effects of the CAR-T cells were evaluated using experimental animals (mice). Results Results revealed that a serum-free, feeder layer-free differentiation system significantly yielded hiPSC-based T cell immunotherapy with interleukin-2, interleukin-15, and activators at the differentiation stage to promote the maturation of these cells into human induced pluripotent stem (hiPS)-T cells. The infection of hiPSCs with the CD19 CAR lentivirus resulted in the production of the hiPSC-CAR-T cells. We validated the function of hiPS-CAR-T cells in vivo and in vitro experimentation which revealed no significant differences in cell morphology and function between hiPSC-derived hiPS-CAR-T cells and peripheral blood-derived CAR-T cells. Conclusions This study developed a culture method that is efficient and clinically useful to make functional CD8+ T cells from hiPSC and to get hiPS-CAR-T cells with high antigen-specific cytotoxicity that are not very different from CAR T cells found in peripheral blood. As a result, our findings may open the way for the clinical use of hiPSC to create functional CD8+ T and hiPS-CAR-T cells cells for use in cell-based cancer therapy.